MAPPING THE LANDSCAPE AND ANALYZING THE SOCIO-ECONOMIC PORTRAITS OF TOMATO VALUE CHAIN IN KANO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
This study identifies and mapped out the tomato value chain actors and the roles played by each actor along the value chain. The actors identified include the Input dealers, Producers (farmers), Marketers (rural assemblers, wholesalers, and retailers), the Processors (hotel, restaurants, industries), transporters and Consumers. Other actors supporting the value chain as extension organizations and research institutes were also identified. Findings of this study (Table 1) reveals the socio-economic portraits like age, gender, educational status, major occupation among other. The study reveals the mean age of the value chain actors approximately as 39 years, 44 years, 44 years, 41 years and 43 years for input dealers, producers, marketers, processors and consumers respectively. The study also reveals that majority of the value chain actors in the area were male and married. The result implies that there is a wide disparity in educational attainment among the value chain actors as findings indicated that only the input dealers in majority (38.5%) attended the formal education system. While, majority of other actors attended the informal education system. Tomato value chain structure in the study area comprises of different forms of marketing channels through which tomatoes flows from initial point of production (farmers) to the end users (consumers). Among all the identified marketing channels, the channels with low number of market intermediaries were considered by the farmers as the most preferred channels because the more the number of market intermediaries the higher the value added and the lower the profit share realized by farmers.
Keywords: Tomato; Value chain; Socio-economic portraits; Marketing channels